Global Trends in Emotional Intelligence Research and Their Implications for Education: A Bibliometric Analysis (2010–2025) - Mai Rosalli Matondang; M Solehuddin; Arie Rakhmat Riyadi; Isma Widiaty; Yohanes Surya (Universitas Pendidikan Mandalika, 2026)
This study aims to analyze the development of emotional intelligence research and its implications for educational practice through a bibliometric analysis of global scientific publications. Using the Scopus Performance Analysis approach, a dataset of 28,404 articles indexed in Scopus between 2010 and 2025 was examined. Descriptive bibliometric techniques were employed, including annual publication trends, author productivity, institutional contributions, and thematic evolution, to identify dominant research patterns and emerging directions. The findings indicate substantial growth in emotional intelligence research over the past decade, peaking in 2021, reflecting increasing attention to social-emotional competencies in education, mental health, and resilience during the COVID-19 pandemic. Thematic analysis shows a shift from early trait-based and self-report approaches toward integrative models linking emotional intelligence with psychological capital, educational outcomes, and emerging digital technologies such as artificial intelligence. These developments underscore the growing recognition of emotional intelligence as a critical factor in supporting student well-being, learning engagement, and adaptive skills in contemporary educational environments. This study provides a comprehensive mapping of emotional intelligence research evolution and identifies key gaps for future studies. For the Indonesian educational context, the findings highlight the importance of integrating emotional intelligence into curriculum design, teacher training, and social-emotional learning initiatives to strengthen students’ psychological resilience and learning readiness in an increasingly complex digital era.